Foreign Exchange Risk Premium : Does Fiscal Policy Matter? Evidence From Italian Data - Giorgianni, Lorenzo (IMF Working Papers; Working Paper ;, 1997)
This paper challenges the conventional view that foreign exchange risk premiums are small, not volatile, and unrelated to macroeconomic variables. For the Italian lira (1987-94), unconditional risk premiums-constructed using survey data to measure exchange rate expectations-are found to be sizable (relative to the dimension of the forward premium), highly volatile (relative to the variability of the forward bias), and predictable. Estimation of structural models of the risk premium suggests that anticipated fiscal contractions in Italy and lower uncertainty about the future path of fiscal policy are associated with a lower risk premium on lira-denominated assets.